UHPC thin-wall electric pole and preparation method thereof
By designing UHPC thin-walled poles and using new materials and modern processes, we have solved the problems of traditional cement treatment, high energy consumption of steam curing, low production efficiency and poor seismic performance in the existing technology, and achieved improvements in pole strength, durability and The improvement of seismic performance reduces production costs and energy consumption.
Patent Information
- Application Number
- CN202411485572.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-21
AI Technical Summary
In the preparation of electric poles, there is a tradition of processing raw materials such as cement in the preparation of electric poles, and the lack of special treatment methods leads to limited performance improvement; steam maintenance energy consumption is large, time is long and operation is complex; production efficiency is low, and automation integration is lacking; there is no bottom of the pole. Reinforced structure, poor seismic resistance; concrete formula lacks new materials, which cannot meet the requirements of modern engineering for high-performance poles.
UHPC thin-walled pole design is adopted. The hollow part is filled with foam plastic. Reinforcing ribs are set on the outer and inner walls. High-strength bolts are used to connect the nodes. Anchor bolts and plug-in connections are used to connect the bottom and the base. A closed cable channel and monitoring are installed inside. The concrete composition of the device includes Portland cement, fly ash beads, slag powder, glass fiber and other new materials, and adopts modern technologies such as microwave curing and intelligent centrifuges.
It improves the strength, durability and seismic performance of poles, reduces production costs and energy consumption, enhances production efficiency and automation integration, extends the service life of poles, and meets the requirements of modern engineering for high-performance poles.
Smart Images

Figure CN119332995A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electric pole preparation and production, and in particular to a UHPC thin-wall electric pole and a preparation method thereof. Background Art
[0002] In the field of modern power and communication, poles are important infrastructure, and their performance and quality are crucial. Traditional pole steel skeletons are usually made of steel. However, with the continuous advancement of science and technology, the emergence of new materials has brought new opportunities for the manufacture of poles. In the field of modern power and communication, poles are important infrastructure, and their performance and quality are crucial. Traditional pole steel skeletons are usually made of steel. However, with the continuous advancement of science and technology, the emergence of new materials has brought new opportunities for the manufacture of poles. In the manufacture of poles, the use of carbon fiber reinforced composite materials to make steel skeletons has many advantages. First, carbon fiber reinforced composite materials have excellent mechanical properties and can provide strong support and stability for poles. Its high strength can withstand greater loads, and its high stiffness can reduce the deformation of poles during use. Secondly, the material has good corrosion resistance and is not as susceptible to erosion by the external environment as steel, thereby extending the service life of the pole. In addition, carbon fiber reinforced composite materials are light in weight, easy to transport and install, and reduce engineering costs. At the same time, it also has good fatigue resistance and seismic resistance, and can adapt to various complex working environments.
[0003] According to a UHPC thin-walled pole and its preparation method with Chinese patent number CN 113149545 A, the concrete used in the thin-walled pole includes cement, silica fume, mineral powder, steel fiber, admixture, machine-made sand, washed sand, coarse aggregate and water, and the weight ratio of each component is: cement 500-550, silica fume 70-80, mineral powder 140-160, steel fiber 55-65, admixture 7-8, machine-made sand 380-420, washed sand 550-650, coarse aggregate 550-650 and water 140-160. The concrete pole prepared by the formula of the present invention uses machine-made sand and washed sand with steel fiber and coarse aggregate, which can greatly improve the strength of the pole, with lower cost and better performance, and the wall thickness can be 30mm, lighter weight, and easy to transport.
[0004] The existing methods have the following problems in actual use: 1. The existing patents are relatively traditional in the treatment of raw materials such as cement, and do not explicitly mention special treatment methods to further improve their performance. The existing patents use steam curing methods, which consume a lot of energy, take a long time to cure, and have complex operations in multiple stages such as heating, constant temperature, and cooling. In addition, the control requirements for parameters such as temperature and humidity are strict. Once there is a deviation, it may affect the maintenance effect of the poles; 2. The existing patented preparation methods have multiple relatively independent links and lack overall automated integration, which may result in low production efficiency. For example, the connection between steel fiber screening, centrifugal forming, steam curing and other steps may not be smooth enough, increasing production time and labor costs; 3. The bottom of the pole in the existing patent has no reinforcement structure and cannot provide good earthquake resistance; 4. The concrete formula in the existing patent mainly includes conventional materials such as cement, silica fume, mineral powder, steel fiber, etc., lacking some new materials with special properties, and cannot fully meet the higher performance requirements of modern engineering for electric poles, and cannot perform well in coping with complex environments and long-term use.
[0005] Therefore, a UHPC thin-walled pole and a preparation method thereof are needed to solve the above problems. Summary of the invention
[0006] Technical issues solved: In view of the shortcomings of the prior art, the present invention provides a UHPC thin-walled pole and a preparation method thereof, which solves the problem that the existing patents treat raw materials such as cement in a relatively traditional way and do not explicitly mention special treatment methods to further improve their performance. The existing patents use a steam curing method, which has high energy consumption, long curing time, and complex operations in multiple stages such as heating, constant temperature, and cooling. In addition, the control requirements for parameters such as temperature and humidity are strict, and once deviations occur, the maintenance effect of the pole may be affected.
[0007] Technical solution: To achieve the above objectives, the present invention is implemented through the following technical solutions: a UHPC thin-walled pole and a preparation method thereof, comprising a thin-walled pole and a base, the thin-walled pole adopts a hollow thin-wall design, the hollow part of the thin-walled pole is filled with foam plastic, the outer wall and the inner wall of the thin-walled pole are provided with reinforcing ribs, the reinforcing ribs of the outer wall and the inner wall of the thin-walled pole can be arranged in three shapes: annular, spiral and longitudinal, the connection nodes of the thin-walled pole are connected by high-strength bolts to ensure the firmness and reliability of the connection, the bottom of the thin-walled pole is connected to the base by anchor bolts and plug-in connection, a cable channel is provided inside the thin-walled pole, power cables and communication cables are laid in the cable channel, the cable channel adopts a closed design to prevent the cables from being affected by the external environment, and the thin-walled pole A monitoring device is installed on the base, and the monitoring device is equipped with a stress sensor, a tilt sensor and a temperature sensor. The monitoring device monitors the stress state, deformation and ambient temperature parameters of the thin-walled pole through the stress sensor, the tilt sensor and the temperature sensor. The monitoring device transmits data to the monitoring center through wireless communication. Side pile blocks are provided on both sides of the base, the bottom of the side pile blocks is deeply buried in the ground, and earthquake monitoring elements are installed on the outside of the side pile blocks. An embedded ring is embedded on the outside of the top of the thin-walled pole, and welding ears are welded on both sides of the embedded ring. Wiredrawing is connected between the top of the side pile blocks on both sides and the welding ears on both sides of the embedded ring. The composition of the concrete of the thin-walled pole includes silicate cement, fly ash beads, slag powder, glass fiber, high-efficiency water reducer, quartz sand, river sand, ceramic particles and deionized water.
[0008] Preferably, the weight ratio of each component of the silicate cement, fly ash microbeads, slag micropowder, glass fiber, high-efficiency water reducing agent, quartz sand, river sand, ceramic particles and deionized water is: 400-500 silicate cement, 80-100 fly ash microbeads, 150-180 slag micropowder, 40-50 glass fiber, 6-8 high-efficiency water reducing agent, 300-350 quartz sand, 400-500 river sand, 400-500 ceramic particles and 120-150 deionized water. Through the precise proportion of the components, the electric pole has high strength, high durability and excellent performance. The silicate cement is a fast-hardening sulphoaluminate cement, which has the characteristics of high early strength and short setting time, meeting the needs of rapid production of electric poles. At the same time, the cement also has good sulfate erosion resistance and antifreeze performance, and is suitable for various harsh environmental conditions. Its unique chemical composition and mineral structure enable the poles to reach higher strength in a shorter period of time, thus improving production efficiency and reducing production costs.
[0009] Preferably, the length of the glass fiber is 10-15 mm, and the surface is specially treated to enhance the bonding strength with concrete. The special surface treatment of the glass fiber is divided into three main items: chemical treatment, physical treatment and composite treatment. The length of the glass fiber is moderate, which can play a good reinforcing role in concrete, but will not cause difficulty in mixing due to excessive length. The special surface treatment can increase the friction and chemical bonding between the glass fiber and concrete, improve the bonding strength between the two, and thus effectively improve the tensile strength and toughness of the pole. The treated glass fiber can work better with concrete, bear external forces together, and extend the service life of the pole. The chemical treatment includes coupling agent treatment and surface coating treatment. The coupling agent treatment uses a silane coupling agent to treat the surface of the glass fiber. One end of the coupling agent molecule reacts chemically with the silanol group on the surface of the glass fiber to form a chemical bond, and the other end combines with the cement hydration product in the concrete. The coupling agent selects γ-aminopropyl triethoxysilane coupling agent, which can form an organic silicon layer on the surface of the glass fiber, enhance the binding force with the inorganic components in the concrete, and improve the bonding strength. The coupling agent treatment can increase the chemical bonding between the glass fiber and the concrete, improve the compatibility of the two, and improve the bonding force. When the surface coating treatment is applied, a special polymer coating is applied to the surface of the glass fiber. The polymer coating can select epoxy resin and polyester. These coatings can increase the surface roughness of the glass fiber and increase the friction between the glass fiber and the concrete. At the same time, the coating can also protect the glass fiber from erosion by the external environment and improve its durability. The use of epoxy resin coating can make the surface of the glass fiber rougher, and it is easier to combine with cement slurry during the concrete mixing process to form a strong bond.
[0010] Preferably, the physical treatment method includes plasma treatment and surface etching. During the plasma treatment, plasma is used to modify the surface of the glass fiber. The high-energy particles in the plasma cause physical and chemical changes on the surface of the glass fiber to increase the surface activity. Polar groups are introduced on the surface of the glass fiber through plasma treatment to improve the interaction with water molecules and cement particles in concrete and enhance the bonding force. Plasma treatment has the advantages of fast processing speed, good effect, and no pollution. During the surface etching, chemical and mechanical methods are used to etch the surface of the glass fiber to increase its surface roughness. The chemical method uses acid and alkali solutions to corrode the surface of the glass fiber to form a microscopic concave-convex structure. Mechanical etching is achieved by sandblasting and grinding. The composite treatment step is a composite treatment with nanomaterials, and nanomaterials are loaded on the surface of the glass fiber. The nanomaterials are selected from nanosilicon dioxide and carbon nanotubes. The nanomaterials can improve the interface performance between the glass fiber and concrete and improve the bonding strength. At the same time, nanomaterials can also enhance the mechanical properties and durability of glass fibers. Nano-silicon dioxide particles are loaded onto the surface of glass fibers by chemical adsorption and physical deposition to form a nano-composite structure, thereby improving the bonding force and collaborative working ability between glass fibers and concrete. The ceramic particles are high-strength wear-resistant ceramics with a particle size of 2-5 mm. High-strength wear-resistant ceramic particles have extremely high hardness and wear resistance, and can significantly improve the compressive strength and wear resistance of electric poles. The smaller particle size allows the ceramic particles to be evenly distributed in the concrete, forming a compact structure, further enhancing the strength and durability of the electric poles. The ceramic particles also have good chemical stability and high temperature resistance, and can maintain the stable performance of the electric poles under various harsh environmental conditions.
[0011] Preferably, the UHPC thin-walled pole and the preparation method thereof, the method comprises the following steps: Sp1. Pole reinforcement: Carbon fiber reinforced composite materials are used to make the steel bar skeleton of the pole. The carbon fiber reinforced composite materials are selected from high-quality carbon fiber prepregs. When preparing the carbon fiber reinforced composite materials, the carbon fiber prepregs are laid on the mold according to the designed laying sequence and fiber direction. Manual laying and automated laying equipment can be used to ensure the uniformity and accuracy of the laying. During the laying process, care should be taken to avoid wrinkles, bubbles and gap defects, and use rollers and vacuum bags for compaction and air removal.
[0012] Sp2. Place the thin-walled pole steel bar skeleton into the pole mold. The mold adopts a detachable design to facilitate demoulding and assembly. The pole mold adopts Fuda's fully automatic pressure-adjustable mold.
[0013] Sp3. Add the proportion of silicate cement, fly ash microbeads, slag powder, high-efficiency water reducing agent, quartz sand, river sand and ceramic particles into a high-powered mixer and mix evenly. Then add deionized water and continue mixing. The glass fiber is evenly dispersed into the concrete by air jet. The high-powered mixer can fully mix the raw materials to improve the uniformity and quality of the concrete. The glass fiber is evenly dispersed into the concrete by air jet to avoid fiber agglomeration and improve the performance stability of thin-walled poles. During the mixing process, the mixing time and speed are strictly controlled.
[0014] Sp4. Place the pole mold on the intelligent centrifuge for centrifugal molding. The intelligent centrifuge automatically adjusts the centrifugal parameters according to the characteristics of the concrete and the specifications of the pole. The intelligent centrifuge automatically adjusts the centrifugal speed, time and acceleration parameters according to the characteristics of the concrete and the specifications of the pole to ensure that the pole reaches the best density and strength during the centrifugal molding process.
[0015] Sp5. Microwave curing is performed on the pole mold and thin-walled pole after centrifugal forming. During the curing process, temperature sensors and humidity sensors are used for real-time monitoring to ensure the curing effect. Through real-time monitoring by temperature sensors and humidity sensors, the temperature and humidity during the curing process are accurately controlled.
[0016] Sp6. After the microwave curing, demoulding is performed, and the thin-walled pole after demoulding is subjected to surface treatment to improve the appearance quality of the thin-walled pole. The thin-walled pole after demoulding is subjected to surface treatment, and the surface treatment steps are divided into three types: grinding, polishing and spraying. The appearance quality of the pole is improved after surface treatment.
[0017] Preferably, the powerful mixer is provided with mixing blades and scrapers inside, and the high-speed and high-torque powerful mixer is used to quickly and fully mix the raw materials to improve the uniformity and quality of the concrete.
[0018] Preferably, the airflow injection device includes a compressed air source, a nozzle and a control system to accurately control the injection amount and direction of the glass fiber. The compressed air source provides strong airflow power to spray the glass fiber into the concrete. The nozzle is used to accurately control the injection amount and direction of the glass fiber to ensure that the fiber is evenly distributed in the concrete. The control system can automatically adjust the injection parameters according to the characteristics of the concrete and the specifications of the poles, thereby improving the degree of production automation and quality stability.
[0019] Preferably, the working mode of the intelligent centrifuge is: slow stage, speed 80r / min, time 3min, speed 160r / min, time 2min; medium speed stage, speed 220r / min, time 1min, speed 260r / min, time 1min; high speed stage, speed 390r / min, time 8min. The three-stage working mode of the intelligent centrifuge gradually increases the centrifugal speed according to the characteristics of concrete and the specifications of thin-walled poles to ensure that the poles achieve the best density and strength during the centrifugal forming process. The slow stage can make the concrete evenly distributed in the mold to avoid segregation. The medium speed stage can further discharge bubbles and excess moisture in the concrete to improve the quality of thin-walled poles. The high speed stage can make the poles reach higher strength in a shorter time and improve production efficiency.
[0020] Preferably, the microwave curing method is: using continuous wave microwaves with a power of 5-10 kW, a curing time of 2-4 hours, and a curing temperature of 60-80°C.
[0021] Preferably, the surface of the thin-walled pole is coated with a waterproof, anti-corrosion and UV-resistant multifunctional coating, which is a composite of nanomaterials and high molecular polymers. The multifunctional coating protects the surface of the thin-walled pole and prevents erosion by moisture, corrosive media and ultraviolet rays.
[0022] Beneficial effects: The present invention provides a UHPC thin-walled pole and a preparation method thereof, which have the following beneficial effects: The present invention adopts fast-hardening sulphoaluminate cement as the main cementitious material, which has the characteristics of high early strength and short setting time, and meets the needs of rapid production. At the same time, the good sulfate corrosion resistance and frost resistance are suitable for various harsh environmental conditions. Compared with the traditional cement of the existing patent, the performance has been significantly improved. The glass fiber is specially treated by chemical, physical and composite treatment to enhance the bonding force with concrete and improve the tensile strength and toughness of the pole. Compared with the steel fiber that has not been specially treated in the existing patent, it can better play a reinforcing role and make the pole more reliable in complex environments. The introduction of new materials such as fly ash microbeads, slag micropowder, ceramic particles, etc., not only improves the density and strength of concrete, but also utilizes industrial waste slag, realizes resource recycling, and reduces environmental pollution. Compared with the conventional materials of the existing patent, it can better meet the high performance requirements of modern engineering for poles.
[0023] The present invention adopts a microwave curing method, which has a short curing time, high efficiency, energy saving and environmental protection. Compared with the existing patented steam curing, it does not need to go through complex heating, constant temperature and cooling stages, is simple to operate, reduces energy consumption and strict control requirements for parameters such as temperature and humidity, reduces the risk of deviations during the curing process, and improves the curing effect and quality stability of the poles. During the curing process, temperature sensors and humidity sensors are used for real-time monitoring, which can accurately control the curing conditions, ensure that the poles are cured in the best curing environment, and further improve the strength and durability of the poles.
[0024] The scheme of the present invention closely cooperates with each link in the preparation process and has a high degree of automation integration. For example, the powerful mixer and air flow injection device ensure the uniformity of concrete and the dispersion of glass fiber; the intelligent centrifuge automatically adjusts the centrifugal parameters according to the characteristics of concrete and the specifications of the pole; the control system automatically adjusts the glass fiber injection parameters, etc. Compared with the relatively independent multiple links in the existing patents, the production efficiency is greatly improved, and the production time and labor costs are reduced.
[0025] In the present invention, the bottom of the pole and the base are connected by anchor bolts and plug-in. At the same time, side pile blocks are provided on both sides of the base. The bottom is deeply buried in the ground, and earthquake monitoring elements are installed on the outside of the side pile blocks. The welding ears on both sides of the embedded ring at the top of the thin-walled pole are connected to the top of the side pile blocks by wire drawing. Compared with the pole bottom without a reinforcement structure in the existing patent, this structural design can better share the horizontal force and bending moment borne by the pole, improve the pole's anti-overturning ability in natural disasters such as strong winds and earthquakes, and play a good anti-seismic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the overall structure of the present invention; Figure 2 It is a structural diagram of the monitoring device of the present invention; Figure 3 It is a schematic diagram of the internal structure of the thin-walled pole of the present invention; Figure 4 A composition map was prepared for the concrete of the present invention.
[0027] Legend: 1. Thin-walled pole; 2. Wire drawing; 3. Welding ear; 4. Embedded ring; 5. Base; 6. Side pile block; 7. Earthquake monitoring element; 8. Monitoring device; 9. Foam plastic; 10. Cable channel; 11. Stress sensor; 12. Tilt sensor; 13. Temperature sensor. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Specific embodiment one: like Figure 1-4 As shown, a UHPC thin-walled pole and a preparation method thereof include a thin-walled pole 1 and a base 5. The thin-walled pole 1 adopts a hollow thin-wall design. The hollow part of the thin-walled pole 1 is filled with foam plastic 9. The outer wall and the inner wall of the thin-walled pole 1 are provided with reinforcing ribs. The reinforcing ribs of the outer wall and the inner wall of the thin-walled pole 1 can be arranged in three shapes: annular, spiral and longitudinal. The connection nodes of the thin-walled pole 1 are connected by high-strength bolts to ensure the firmness and reliability of the connection. The bottom of the thin-walled pole 1 is connected to the base 5 by anchor bolts and plug-in connection. A cable channel 10 is provided inside the thin-walled pole 1. Power cables and communication cables are laid in the cable channel 10. The cable channel 10 adopts a closed design to prevent the cables from being affected by the external environment. A monitoring device 8 is installed on the thin-walled pole 1, and the monitoring device 8 is equipped with A stress sensor 11, a tilt sensor 12 and a temperature sensor 13 are provided. The monitoring device 8 monitors the stress state, deformation and ambient temperature parameters of the thin-walled pole 1 through the stress sensor 11, the tilt sensor 12 and the temperature sensor 13. The monitoring device 8 transmits data to the monitoring center through wireless communication. Side pile blocks 6 are provided on both sides of the base 5. The bottom of the side pile block 6 is deeply buried in the ground. An earthquake monitoring element 7 is installed on the outer side of the side pile block 6. An embedded ring 4 is embedded on the outside of the top of the thin-walled pole 1. Welding ears 3 are welded on both sides of the embedded ring 4. A wire drawing 2 is connected between the top of the side pile blocks 6 on both sides and the welding ears 3 on both sides of the embedded ring 4. The composition of the concrete of the thin-walled pole includes silicate cement, fly ash microbeads, slag micropowder, glass fiber, high-efficiency water reducing agent, quartz sand, river sand, ceramic particles and deionized water.
[0030] The hollow thin-walled structure of the entire thin-walled pole 1 can effectively reduce the weight of the pole and reduce the transportation and installation costs. At the same time, under the premise of meeting the strength requirements, the amount of material used is reduced, which is more energy-saving and environmentally friendly. The hollow part is filled with foam plastic 9, which can further reduce the weight on the one hand, and on the other hand, the foam plastic 9 can also play a certain role in heat preservation and sound insulation, reducing the impact of the external environment on the cable. Reinforcement ribs are set on the outer wall and the inner wall, and there are three types of layout: annular, spiral and longitudinal. Different layout methods can enhance the strength and rigidity of the pole in different directions. The annular reinforcement ribs can improve the annular compressive resistance of the pole; the spiral reinforcement ribs perform well when subjected to torque; the longitudinal reinforcement ribs help to improve the axial bearing capacity of the pole. By reasonably selecting the layout of the reinforcement ribs, the design can be optimized according to the specific use environment and stress conditions to improve the overall performance of the pole. The connection nodes are connected with high-strength bolts to ensure the firmness and reliability of the connection. High-strength bolts can withstand large tensile and shear forces, ensuring that the poles will not become loose or fail under various external forces. The bottom and the base are connected by anchor bolts and plug-in connections. This connection method can firmly fix the poles on the base and improve the stability of the poles. Anchor bolts can provide strong anchoring force, and plug-in connections are easy to install and disassemble, convenient for maintenance and replacement. A closed cable channel is set inside to provide a safe laying environment for power cables and communication cables. The closed design can prevent the cables from being eroded by the external environment, such as rain, dust, ultraviolet rays, etc., and extend the service life of the cables. Monitoring devices are installed, equipped with stress sensors, tilt sensors and temperature sensors, which can monitor the stress state, deformation and ambient temperature parameters of the poles in real time. Data is transmitted to the monitoring center through wireless communication, which is convenient for managers to understand the operating status of the poles in a timely manner, find problems and take corresponding measures for maintenance and repair.
[0031] Side pile blocks 6 are arranged on both sides of the base 5, and the bottom is deeply buried in the ground, which increases the stability of the pole system. The side pile blocks 6 can share the horizontal force and bending moment borne by the pole, and improve the pole's anti-overturning ability in natural disasters such as strong winds and earthquakes. Earthquake monitoring elements 7 are installed on the outside of the side pile blocks 6, which can monitor earthquake activities in real time and provide data support for the seismic design of the pole. When an earthquake occurs, an alarm can be issued in time, and corresponding emergency measures can be taken to ensure the safe operation of the power and communication systems. The welding ears 3 on both sides of the embedded ring 4 at the top of the thin-walled pole 1 are connected to the top of the side pile block 6, which further enhances the stability of the pole. The wire drawing 2 can withstand a certain pulling force to prevent the pole from tilting or collapsing when subjected to external forces. The entire pole is mainly composed of the thin-walled pole 1 body and the base 5.
[0032] Analysis of concrete components: Portland cement: As the main cementitious material, it provides strength and stability for concrete. Different types of Portland cement have different performance characteristics and can be selected according to specific requirements. For example, fast-hardening sulphoaluminate cement has the characteristics of high early strength and short setting time, which is suitable for projects that require fast construction.
[0033] Fly ash microbeads and slag micropowder: Fly ash microspheres and slag micropowder are recycled products of industrial waste residues, with good activity and filling properties. They can react with cement hydration products to generate more cementitious substances and improve the strength and durability of concrete.
[0034] At the same time, the addition of fly ash microbeads and slag micropowder can also reduce the amount of cement used, reduce the cost of concrete, and reduce pollution to the environment.
[0035] Glass fiber: As a reinforcing material, it can significantly improve the tensile strength and toughness of concrete. Glass fiber forms a three-dimensional randomly distributed mesh structure in concrete, effectively preventing the expansion of cracks and improving the crack resistance of the pole. The glass fiber with special surface treatment has a stronger bond with concrete and can better play a reinforcing role.
[0036] High-efficiency water reducing agent: It can reduce the water-cement ratio of concrete and improve the strength and durability of concrete. At the same time, high-efficiency water reducing agent can also improve the workability of concrete, making it easier to construct and shape.
[0037] Quartz sand and river sand: As fine aggregate, they provide filling and support for concrete. Quartz sand has high hardness and stability, while river sand has good gradation and fluidity. The reasonable combination of the two can improve the density and strength of concrete.
[0038] Ceramic particles: High-strength and wear-resistant ceramic particles have extremely high hardness and wear resistance, which can significantly improve the compressive strength and wear resistance of the poles. The smaller particle size allows the ceramic particles to be evenly distributed in the concrete, forming a compact structure, further enhancing the strength and durability of the poles. At the same time, ceramic particles also have good chemical stability and high temperature resistance, which can maintain the stable performance of the poles under various harsh environmental conditions.
[0039] Deionized water: ensures the purity of concrete and avoids the adverse effects of impurities in water on concrete performance. Deionized water can fully react with cement and other cementitious materials to generate more stable hydration products, thereby improving the strength and durability of concrete.
[0040] This UHPC thin-walled pole and its preparation method have the characteristics of reasonable structure, excellent performance, and complete functions. By adopting innovative structures such as hollow thin-wall design, reinforcement arrangement, cable channel and monitoring device, and optimizing the composition of concrete, the strength, durability, stability and safety of the pole are improved, providing a reliable infrastructure guarantee for the development of the power and communication industries. Specific embodiment 2: like Figure 1-4 As shown in the figure, the weight ratio of each component of silicate cement, fly ash microbeads, slag micropowder, glass fiber, high-efficiency water reducing agent, quartz sand, river sand, ceramic particles and deionized water is: silicate cement 400-500, fly ash microbeads 80-100, slag micropowder 150-180, glass fiber 40-50, high-efficiency water reducing agent 6-8, quartz sand 300-350, river sand 400-500, ceramic particles 400-500 and deionized water 120-150. Through the precise proportion of the components, the electric pole has high strength, high durability and excellent performance. The silicate cement is a fast-hardening sulphoaluminate cement. The fast-hardening sulphoaluminate cement has the characteristics of high early strength and short setting time, which meets the needs of rapid production of electric poles. At the same time, the cement also has good sulfate erosion resistance and antifreeze performance, and is suitable for various harsh environmental conditions. Its unique chemical composition and mineral structure enable the poles to reach higher strength in a shorter period of time, thus improving production efficiency and reducing production costs.
[0042] The length of the glass fiber is 10-15mm, and the surface is specially treated to enhance the bonding with concrete. The special treatment of the glass fiber surface is divided into three main items: chemical treatment, physical treatment and composite treatment. The length of the glass fiber is moderate, which can play a good reinforcing role in concrete, but will not cause mixing difficulties due to excessive length. The special surface treatment can increase the friction and chemical bonding between the glass fiber and concrete, improve the bonding strength of the two, and thus effectively improve the tensile strength and toughness of the pole. The treated glass fiber can work better with concrete, bear external forces together, and extend the service life of the pole. The chemical treatment includes coupling agent treatment and surface coating treatment. When the coupling agent is treated, the surface of the glass fiber is treated with a silane coupling agent. One end of the coupling agent molecule reacts chemically with the silanol group on the surface of the glass fiber to form a chemical bond, and the other end combines with the cement hydration product in the concrete. The coupling agent is selected as γ-aminopropyl triethoxysilane coupling agent, which can form an organic silicon layer on the surface of the glass fiber, enhance the binding force with the inorganic components in the concrete, and improve the bonding strength. The coupling agent treatment can increase the chemical bonding between the glass fiber and the concrete, improve the compatibility between the two, and improve the bonding force. When the surface coating is treated, a special polymer coating is applied to the surface of the glass fiber. The polymer coating can choose epoxy resin and polyester. These coatings can increase the surface roughness of the glass fiber and increase the friction between the glass fiber and the concrete. At the same time, the coating can also protect the glass fiber from erosion by the external environment and improve its durability. The use of epoxy resin coating can make the surface of the glass fiber rougher, and it is easier to combine with cement slurry during the concrete mixing process to form a strong bond.
[0043] Physical treatment methods include plasma treatment and surface etching. During plasma treatment, plasma is used to modify the surface of glass fiber. The high-energy particles in the plasma cause physical and chemical changes on the surface of the glass fiber, increasing the surface activity. Polar groups are introduced on the surface of the glass fiber through plasma treatment to improve the interaction with water molecules and cement particles in concrete and enhance the bonding force. Plasma treatment has the advantages of fast processing speed, good effect and no pollution. During surface etching, chemical and mechanical methods are used to etch the surface of the glass fiber to increase its surface roughness. Chemical methods use acid and alkali solutions to corrode the surface of the glass fiber to form a microscopic concave-convex structure. Mechanical etching is achieved by sandblasting and grinding. The composite treatment step is composite treatment with nanomaterials. Nanomaterials are loaded on the surface of the glass fiber. Nanomaterials are selected from nanosilicon dioxide and carbon nanotubes. Nanomaterials can improve the interface performance between glass fiber and concrete and improve bonding strength. At the same time, nanomaterials can also enhance the mechanical properties and durability of glass fibers. Nano-silicon dioxide particles are loaded onto the surface of glass fibers by chemical adsorption and physical deposition to form a nano-composite structure, which improves the bonding force and collaborative working ability between glass fibers and concrete. Ceramic particles are high-strength wear-resistant ceramics with a particle size of 2-5 mm. High-strength wear-resistant ceramic particles have extremely high hardness and wear resistance, which can significantly improve the compressive strength and wear resistance of electric poles. The smaller particle size allows ceramic particles to be evenly distributed in concrete to form a tight structure, further enhancing the strength and durability of electric poles. Ceramic particles also have good chemical stability and high temperature resistance, which can maintain the stable performance of electric poles under various harsh environmental conditions.
[0044] The precise proportion of ingredients enables each material to work together to achieve optimal performance. As the main cementitious material, silicate cement provides a strength foundation for the poles in the range of 400-500 parts by weight. The characteristics of fast-hardening sulphoaluminate cement make it suitable for rapid production, while performing well in harsh environments, reducing production costs and improving production efficiency. The weight ratio of fly ash microbeads is 80-100, and the ratio of slag micropowder is 150-180, which not only improves the density of concrete, but also utilizes industrial waste residues, realizes resource recycling, and reduces environmental pollution. The ratio of glass fiber is 40-50, with a length of 10-15mm. After special treatment, it enhances the bonding force with concrete and effectively improves the tensile strength and toughness of the pole. The ratio of high-efficiency water reducer is 6-8, which optimizes the workability of concrete, reduces the water-cement ratio, and improves strength and durability. The ratio of quartz sand 300-350 and river sand 400-500, as fine aggregate, together with ceramic particles 400-500 constitute the concrete skeleton, ensuring the strength and stability of the pole. The ratio of deionized water is 120-150, which ensures the purity of concrete and promotes chemical reactions between the components.
[0045] Chemical treatment: In the coupling agent treatment, the γ-aminopropyltriethoxysilane coupling agent reacts with the silanol groups on the surface of the glass fiber to form a chemical bond, and the other end combines with the cement hydration product to enhance the bonding strength. This treatment improves the compatibility of glass fiber and concrete and increases the bonding strength.
[0046] The surface coating treatment uses polymer coatings such as epoxy resin and polyester to increase the surface roughness of the glass fiber, improve the friction with the concrete, and at the same time protect the glass fiber from external erosion and improve durability.
[0047] Physical treatment: Plasma treatment uses high-energy particles to cause physical and chemical changes on the surface of glass fibers, increase surface activity, introduce polar groups, improve interaction with water molecules and cement particles in concrete, and enhance bonding strength. The treatment is fast, effective, and pollution-free.
[0048] Surface etching uses chemical and mechanical methods. The chemical method uses acid and alkaline solutions to corrode the surface of the glass fiber to form a microscopic concave-convex structure. Mechanical etching is achieved through sandblasting and grinding, which increases the surface roughness of the glass fiber.
[0049] Composite treatment: Composite treatment with nano materials, nano silicon dioxide and carbon nanotubes are selected to load on the surface of glass fiber to form a nano composite structure. The interface performance between glass fiber and concrete is improved, the bonding strength is increased, and the mechanical properties and durability of glass fiber are enhanced.
[0050] The particle size of high-strength wear-resistant ceramic particles is 2-5mm, with extremely high hardness and wear resistance, which significantly improves the compressive strength and wear resistance of the poles. Evenly distributed in the concrete to form a compact structure, it enhances the strength and durability of the poles. Good chemical stability and high temperature resistance enable it to maintain stable performance in various harsh environments. Stability of the production process: The precise ratio of ingredients requires high stability of the production process. In actual production, how to ensure accurate measurement and uniform mixing of each component is a key issue. For example, if the amount of high-efficiency water reducer added is inaccurate, it may affect the workability and strength of the concrete.
[0051] Cost and complexity of glass fiber processing: Although special surface treatment methods for glass fibers can improve performance, they also increase production costs and process complexity. Coupling agent treatment, surface coating treatment, plasma treatment and composite treatment all require specific equipment and technology, which may increase the difficulty and cost of production.
[0052] Supply and quality stability of ceramic particles: Whether the supply of high-strength wear-resistant ceramic particles is stable and the consistency of their quality is also a question that needs to be considered. If the performance of ceramic particles in different batches varies greatly, it may affect the quality stability of the poles.
[0053] Long-term verification of environmental adaptability: Although the material has good resistance to sulfate erosion, frost resistance and high temperature resistance in theory, its environmental adaptability needs to be further verified during actual long-term use. For example, whether the performance of the pole can remain stable under the climatic conditions and soil environment of different regions.
[0054] Sustainable development considerations: In the selection and production process of materials, sustainable development factors can be further considered, such as reducing the impact on the environment, improving the efficiency of resource utilization, and exploring recyclable and degradable materials. Specific embodiment three: like Figure 1-4 As shown, a method for preparing a UHPC thin-walled pole comprises the following steps: Sp1. Pole reinforcement: The steel skeleton of the pole is made of carbon fiber reinforced composite materials, which has high strength and corrosion resistance. Carbon fiber reinforced composite materials have extremely high strength and rigidity, and are lighter and more corrosion-resistant than traditional steel. The use of this material to make the steel skeleton of the pole can greatly improve the carrying capacity and durability of the pole and extend the service life of the pole. At the same time, the use of carbon fiber reinforced composite materials can also reduce the dead weight of the pole, making it easier to transport and install.
[0056] Sp2. Put the steel bar skeleton of the electric pole into the electric pole mold. The mold adopts a detachable design, which is convenient for demoulding and assembly. The electric pole mold adopts Fuda's fully automatic pressure-adjustable mold. The detachable mold design makes the production of electric poles more flexible and efficient. When demoulding, you only need to disassemble the mold to easily remove the electric pole, avoiding the problem of difficult demoulding of traditional molds. At the same time, the detachable mold is also easy to assemble and adjust, and can be customized according to different pole specifications and shapes, improving the adaptability of production.
[0057] Sp3. Add the proportion of silicate cement, fly ash microbeads, slag powder, high-efficiency water reducing agent, quartz sand, river sand and ceramic particles into a high-powered mixer and mix evenly. Then add deionized water and continue mixing. The glass fiber is evenly dispersed into the concrete by air jet. The high-powered mixer can fully mix the raw materials to improve the uniformity and quality of the concrete. The glass fiber is evenly dispersed into the concrete by air jet to avoid the problem of fiber agglomeration and improve the performance stability of the pole. During the mixing process, the mixing time and speed are strictly controlled to ensure that the concrete achieves the best workability and strength.
[0058] Sp4. Place the pole mold on the intelligent centrifuge for centrifugal molding. The intelligent centrifuge automatically adjusts the centrifugal parameters according to the characteristics of the concrete and the specifications of the pole, and automatically adjusts the centrifugal speed, time and acceleration parameters according to the characteristics of the concrete and the specifications of the pole to ensure that the pole reaches the best density and strength during the centrifugal molding process. Centrifugal molding can effectively remove bubbles and excess water in the concrete and improve the quality and performance of the pole.
[0059] Sp5. The pole mold and the pole after centrifugal forming are subjected to microwave curing together. During the curing process, temperature sensors and humidity sensors are used for real-time monitoring to ensure the curing effect. Microwave curing has the advantages of short curing time, high efficiency, energy saving and environmental protection. Through real-time monitoring by temperature sensor 13 and humidity sensor, the temperature and humidity during the curing process are accurately controlled to ensure that the pole is cured under the best curing conditions, thereby improving the strength and durability of the pole.
[0060] Sp6. After microwave curing, the poles are demoulded and surface treated to improve the appearance quality of the poles. The surface treatment steps are divided into three types: grinding, polishing and spraying. The surface treatment can also improve the waterproof, anti-corrosion and anti-ultraviolet performance of the poles and extend the service life of the poles. Specific embodiment four: like Figure 1-4 As shown, the powerful mixer has the characteristics of high speed and high torque, which can ensure the full mixing of concrete. The mixer is equipped with mixing blades and scrapers to prevent the concrete from sticking to the wall and agglomerating. The high speed and high torque powerful mixer can fully mix the raw materials in a short time to improve the uniformity and quality of the concrete. The setting of mixing blades and scrapers can effectively prevent the concrete from sticking to the wall and agglomerating, ensuring the smooth progress of the mixing process. At the same time, the shape and layout of the mixing blades and scrapers are optimized to maximize the mixing efficiency and reduce the mixing time and energy consumption.
[0062] The airflow injection device includes a compressed air source, a nozzle and a control system to accurately control the injection amount and direction of the glass fiber. The compressed air source provides a strong airflow power to spray the glass fiber into the concrete. The nozzle is used to accurately control the injection amount and direction of the glass fiber to ensure that the fiber is evenly distributed in the concrete. The control system can automatically adjust the injection parameters according to the characteristics of the concrete and the specifications of the poles, thereby improving the degree of production automation and quality stability.
[0063] The working mode of the intelligent centrifuge is: slow stage, speed 80r / min, time 3min, speed 160r / min, time 2min; medium speed stage, speed 220r / min, time 1min, speed 260r / min, time 1min; high speed stage, speed 390r / min, time 8min. The three-stage working mode of the intelligent centrifuge gradually increases the centrifugal speed according to the characteristics of concrete and the specifications of the pole to ensure that the pole reaches the best density and strength during the centrifugal forming process. The slow stage can make the concrete evenly distributed in the mold to avoid segregation. The medium speed stage can further discharge bubbles and excess water in the concrete to improve the quality of the pole. The high speed stage can make the pole reach higher strength in a shorter time and improve production efficiency.
[0064] The microwave curing method is: using continuous wave microwave, the power is 5-10kW, the curing time is 2-4 hours, the curing temperature is 60-80℃, continuous wave microwave curing can make the pole reach a higher strength in a shorter time, and improve production efficiency. Reasonable selection of power, curing time and curing temperature can ensure that the pole achieves the best performance during the curing process. At the same time, microwave curing also has the advantages of energy saving, environmental protection, simple operation, etc., which is suitable for large-scale production.
[0065] The surface of the pole is coated with a multifunctional coating that is waterproof, anti-corrosive and anti-ultraviolet. The coating is made of a composite of nanomaterials and high molecular polymers, and has good adhesion and durability. The multifunctional coating can protect the surface of the pole from moisture, corrosive media and ultraviolet erosion, and extend the service life of the pole. The addition of nanomaterials can improve the density and wear resistance of the coating and enhance the protective performance of the coating. The high molecular polymer gives the coating good adhesion and flexibility, so that it can better adapt to the shape changes and external forces on the surface of the pole. The construction process of the coating has been optimized to ensure that the coating is firmly bonded to the surface of the pole and is not easy to fall off.
[0066] The UHPC thin-walled pole preparation method includes the steps of pole reinforcement, mold use, material mixing, centrifugal molding, microwave curing and post-demolding treatment. The performance of the pole is improved by using carbon fiber reinforced composite materials to make the steel skeleton; the detachable mold is convenient for demoulding and assembly; the powerful mixer and air jet device ensure the uniformity of concrete and the dispersion of glass fiber; the intelligent centrifuge works in stages to achieve the best density and strength; microwave curing is efficient and can accurately control temperature and humidity; post-demolding surface treatment and multifunctional coating extend the service life of the pole. Pole reinforcement: Cost analysis of carbon fiber reinforced composite materials: Although it has many advantages, carbon fiber materials are more expensive than traditional steel materials, which may increase the initial cost of the poles. In practical applications, its long-term performance advantages and cost-effectiveness need to be considered comprehensively.
[0067] Interface bonding between carbon fiber and concrete: Although carbon fiber reinforced composites have high strength and corrosion resistance, the interface bonding between carbon fiber and concrete is still a key issue. During the preparation process, it is necessary to ensure good adhesion between carbon fiber and concrete to give full play to the reinforcing effect of carbon fiber. Further research can be conducted to optimize the surface treatment method of carbon fiber or add interface enhancers to improve the interface bonding performance.
[0068] Mould design: Sealing performance of the split mold: During the assembly process of the split mold, the sealing performance between the various parts is crucial. If the sealing is poor, it may cause leakage of concrete during pouring and centrifugal molding, affecting the quality of the pole. Therefore, it is necessary to optimize the sealing structure of the mold and strictly check the sealing performance during use.
[0069] Durability of mold: Since pole production may be a long process, the mold needs to withstand multiple uses and disassembly and assembly. Therefore, the material selection and structural design of the mold should take into account its durability to ensure that it can maintain good performance and precision during long-term use.
[0070] Mixing process: Control accuracy of mixing time and speed: Strict control of mixing time and speed is very important to ensure that concrete achieves optimal workability and strength. However, in actual production, the control accuracy of mixing equipment may be affected by many factors, such as changes in the properties of raw materials, equipment wear, etc. Therefore, it is necessary to establish an effective mixing process monitoring system to adjust the mixing parameters in real time to ensure the stability of concrete quality.
[0071] Sequence of adding raw materials: The order of adding different raw materials may have an impact on the properties of concrete. Further research can be done to optimize the order of adding raw materials during the mixing process to improve the uniformity and properties of concrete.
[0072] Centrifugal Forming: Stress distribution during centrifugal forming: During the centrifugal forming process, complex stress distribution will be generated inside the pole. If the stress distribution is uneven, it may cause cracks or deformation in the pole. Therefore, it is necessary to deeply understand the stress distribution law during the centrifugal forming process through numerical simulation and experimental research, and take corresponding measures to optimize the centrifugal parameters and reduce stress concentration.
[0073] The influence of centrifugal molding on the distribution of glass fibers: The centrifugal molding process may have an impact on the distribution of glass fibers. It is necessary to study the movement law of glass fibers during centrifugal molding to ensure that the glass fibers can still be evenly distributed in the concrete to fully exert their reinforcing effect.
[0074] Microwave curing: Uniformity of microwave curing: During the microwave curing process, it is necessary to ensure that the temperature and humidity inside the pole are evenly distributed to ensure stable performance of the pole. The uniformity of microwave curing can be improved by optimizing the design of microwave curing equipment, such as using multiple antenna arrangements and rotating platforms.
[0075] Comparative study of microwave curing and traditional curing methods: Although microwave curing has many advantages, its applicability and long-term performance under different environmental conditions need further study compared with traditional methods such as steam curing. Comparative experiments can be conducted to analyze the effects of microwave curing and traditional curing methods on the performance of poles, providing a more scientific basis for actual production.
[0076] Post-demolding treatment: Process stability of surface treatment: Surface treatment steps such as grinding, polishing and spraying need to ensure process stability to ensure the consistency of the appearance quality and protective performance of the poles. Strict process standards and quality control systems can be established to monitor and inspect the surface treatment process.
[0077] Long-term performance of multifunctional coatings: Although multifunctional coatings have good waterproof, anti-corrosion and UV resistance, their performance may be gradually degraded by environmental factors during long-term use. Long-term outdoor exposure tests are required to study the durability of multifunctional coatings so that they can be maintained and updated when necessary. Specific embodiment five: like Figure 1-4 As shown, the following formula is used in the above preparation method: 1. Optimization of concrete composition ratio 1. A multi-objective optimization model based on performance indicators such as strength and durability can be established, and the optimal weight ratio of silicate cement, fly ash microbeads, slag micropowder, glass fiber, high-efficiency water reducer, quartz sand, river sand, ceramic particles and deionized water can be determined by introducing optimization algorithms such as genetic algorithm and particle swarm optimization algorithm.
[0079] For example, the objective function is set to maximize the strength and durability of the pole and minimize the cost, while considering the constraints between the components, such as the total weight limit, the water-cement ratio range, etc. The optimization algorithm is used to iterate and search for the optimal combination of component ratios.
[0080] The formula can be expressed as: ; in Indicates strength, Indicates durability, Respectively represent the weight of each component, is the expression of the objective function.
[0081] At the same time, the constraints are met: ; in is the constraint function, is the constraint value.
[0082] For the length and surface treatment parameters of glass fibers, a mathematical model related to concrete performance can be established, and the best length range and treatment method combination can be determined through an optimization algorithm.
[0083] For example, to model the relationship between glass fiber length and pole tensile strength: ; in Represents tensile strength, Represents the length of the glass fiber, and then the optimization algorithm is used to find the length value that maximizes the tensile strength. For the surface treatment parameters, such as the amount of coupling agent, the thickness of the coating, etc., a similar model can be established for optimization.
[0084] 2. Centrifugal Forming Parameter Optimization The stress distribution model of the pole during the centrifugal forming process was established using numerical simulation methods, and then the centrifugal speed, time, acceleration and other parameters were adjusted through optimization algorithms to minimize stress concentration and deformation.
[0085] For example, the finite element analysis method is used to calculate the stress distribution of the pole under different centrifugal parameters and establish the stress function: ; The stress function represents stress, represents the centrifugal speed, Indicates time, represents the acceleration, and then the centrifugal parameter combination that minimizes the stress is found through the optimization algorithm.
[0086] The formula can be expressed as: ; At the same time, it meets the constraints such as the process requirements of centrifugal forming and the quality standards of electric poles.
[0087] For the distribution of glass fibers during centrifugal molding, a model based on fluid mechanics and particle motion can be established, and the optimal centrifugal parameters can be determined through optimization algorithms to ensure uniform distribution of glass fibers. For example, the motion equation of glass fibers in concrete is established, considering the influence of factors such as centrifugal force and friction, and the centrifugal parameters that make the glass fibers most evenly distributed are found through numerical simulation and optimization algorithms.
[0088] Optimization of microwave curing parameters: A temperature and humidity distribution model of the pole during microwave maintenance is established, and parameters such as microwave power, maintenance time and maintenance temperature are adjusted through optimization algorithm to achieve the best maintenance effect.
[0089] For example, the heat conduction equation and moisture diffusion equation are used to establish a model for the temperature and humidity changes of the pole during microwave curing. and ; in Indicates temperature, Indicates humidity, represents microwave power, Indicates time, Indicates the curing temperature. represents the initial humidity. Then, an optimization algorithm is used to find the parameter combination that makes the temperature and humidity distribution most uniform and the curing effect best.
[0090] The formula can be expressed as: ; The maintenance effect refers to the performance index of the pole after maintenance. is the objective function, It is the relationship function between the curing effect and the temperature, humidity and microwave parameters.
[0091] By adding these algorithm formulas, the entire solution can be made more scientific, precise and innovative, improving the performance and quality of the poles while reducing production costs and improving production efficiency. Specific embodiment six: like Figure 1-4 As shown, the above scheme can be concluded to be better than the existing technology through the following experimental methods: 1. Purpose of the test Verify the performance of UHPC thin-walled poles and their preparation methods, including strength, durability, stability, etc., and optimize the preparation process parameters.
[0093] 2. Test Materials Portland cement (rapid hardening sulphoaluminate cement), fly ash microbeads, slag micropowder, glass fiber (length 10-15mm, specially treated), high-efficiency water reducer, quartz sand, river sand, ceramic particles, deionized water.
[0094] Carbon fiber reinforced composite materials (used to make steel bar skeletons for electric poles).
[0095] Detachable electric pole mould (Fuda fully automatic pressure adjustable mould).
[0096] Powerful mixer, air jet device, intelligent centrifuge, microwave curing equipment.
[0097] Temperature sensor 13, humidity sensor, stress sensor 11, tilt sensor 12, earthquake monitoring element, etc.
[0098] 3. Test steps Concrete component ratio test Prepare multiple groups of concrete materials with different weight ratios, and combine them according to the range of Portland cement (400-500), fly ash microbeads (80-100), slag micropowder (150-180), glass fiber (40-50), high-efficiency water reducer (6-8), quartz sand (300-350), river sand (400-500), ceramic particles (400-500) and deionized water (120-150).
[0099] Use a high-powered blender to blend the ingredients until smooth, carefully controlling the blending time and speed.
[0100] Concrete specimens were made for strength tests (compressive strength, tensile strength) and durability tests (resistance to sulfate attack, frost resistance).
[0101] The optimal concrete component ratio is determined through test results.
[0102] Glass fiber surface treatment effect test: Three groups of glass fibers were prepared and subjected to chemical treatment (coupling agent treatment and surface coating treatment), physical treatment (plasma treatment and surface etching), and composite treatment (composite treatment with nanomaterials).
[0103] The treated glass fibers were added into concrete in the same proportion to make test specimens.
[0104] Strength tests and durability tests were conducted to compare the effects of glass fiber on concrete performance under different treatment methods.
[0105] Pole reinforcement skeleton test: Two groups of electric pole steel skeletons were made, one group using traditional steel and the other using carbon fiber reinforced composite materials. The steel skeletons were placed in electric pole molds, and electric poles were made using the same preparation method. The poles were tested for load-bearing capacity and corrosion resistance, and the performance differences between the two materials were compared.
[0106] Centrifugal forming parameter test: Set different combinations of centrifugal speed, time and acceleration parameters. For example, the working mode of the intelligent centrifuge is: slow stage (speed 70-90r / min, time 2-4min), medium speed stage (speed 200-240r / min, time 1-2min), high speed stage (speed 380-420r / min, time 7-9min).
[0107] Different parameter combinations were used for centrifugal forming to produce pole specimens.
[0108] Check the density and strength of the specimens and determine the optimal centrifugal parameters based on the test results.
[0109] Microwave curing parameter test: Set different parameter combinations of microwave power (4-6kW, 6-8kW, 8-10kW), curing time (1-3 hours, 2-4 hours, 3-5 hours) and curing temperature (50-70℃, 60-80℃, 70-90℃).
[0110] The pole mold and pole after centrifugal forming are subjected to microwave curing together, and temperature sensors and humidity sensors are used for real-time monitoring to test the strength and durability of the pole after curing and determine the optimal microwave curing parameters.
[0111] Overall performance test: UHPC thin-walled poles are manufactured according to the optimal concrete component ratio, glass fiber processing method, steel skeleton material, centrifugal forming parameters and microwave curing parameters.
[0112] Conduct comprehensive performance tests on the poles, including strength, durability, stability (install monitoring devices to test stress status, deformation and ambient temperature parameters), and anti-overturning ability (use side pile blocks and seismic monitoring elements to simulate strong winds, earthquakes and other natural disasters) to verify whether the poles meet the design requirements and actual use needs.
[0113] 4. Data Recording and Analysis Record all parameters and test results in each test step, including concrete composition ratio, glass fiber processing method, centrifugal speed, time and acceleration, microwave power, curing time and temperature, pole strength, durability, stability and other data.
[0114] Analyze the test data, compare the performance differences under different parameters, and determine the optimal preparation process parameters.
[0115] Use charts and other methods to intuitively display the test results for better understanding and analysis.
[0116] 5. Notes Strictly follow the test steps to ensure the accuracy and repeatability of the test.
[0117] Pay attention to safety, especially when using high-powered mixers, intelligent centrifuges and microwave curing equipment, and follow the operating procedures.
[0118] The test materials should be properly stored to prevent them from getting damp, deteriorating, etc. which may affect the test results.
[0119] Record problems and abnormal situations during the test in a timely manner for analysis and improvement.
[0120] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the statement "comprising a reference structure" do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0121] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A UHPC thin-walled pole and a method for manufacturing the same, comprising a thin-walled pole (1) and a base (5), characterized in that: The thin-walled pole (1) adopts a hollow thin-wall design, the hollow part of the thin-walled pole (1) is filled with foam plastic (9), the outer wall and the inner wall of the thin-walled pole (1) are provided with reinforcing ribs, and the reinforcing ribs of the outer wall and the inner wall of the thin-walled pole (1) can be arranged in three shapes: annular, spiral and longitudinal. The connection nodes of the thin-walled pole (1) are connected by high-strength bolts to ensure the firmness and reliability of the connection. The bottom of the thin-walled pole (1) is connected to the base (5) by anchor bolts and plug-in connection. A cable channel (10) is arranged inside the thin-walled pole (1), and power cables and communication cables are laid in the cable channel (10). The cable channel (10) adopts a closed design to prevent the cables from being affected by the external environment. A monitoring device (8) is installed on the thin-walled pole (1), and the monitoring device (8) is equipped with a stress sensor (11), a tilt sensor (12) and The monitoring device (8) monitors the stress state, deformation and ambient temperature parameters of the thin-walled pole (1) through the stress sensor (11), the tilt sensor (12) and the temperature sensor (13); the monitoring device (8) transmits data to the monitoring center through wireless communication; side pile blocks (6) are provided on both sides of the base (5); the bottom of the side pile blocks (6) is deeply buried in the ground; the outer side of the side pile blocks (6) is installed with an earthquake monitoring element (7); the outer side of the top of the thin-walled pole (1) is embedded with an embedded ring (4); welding ears (3) are welded on both sides of the embedded ring (4); a wire drawing (2) is connected between the top of the side pile blocks (6) on both sides and the welding ears (3) on both sides of the embedded ring (4); the concrete of the thin-walled pole comprises silicate cement, fly ash microbeads, slag micropowder, glass fiber, high-efficiency water reducing agent, quartz sand, river sand, ceramic particles and deionized water.
2. A UHPC thin-walled pole and a method for preparing the same according to claim 1, characterized in that: The weight proportions of the components of the silicate cement, fly ash microbeads, slag micropowder, glass fiber, high-efficiency water reducing agent, quartz sand, river sand, ceramic particles and deionized water are as follows: 400-500 parts of silicate cement, 80-100 parts of fly ash microbeads, 150-180 parts of slag micropowder, 40-50 parts of glass fiber, 6-8 parts of high-efficiency water reducing agent, 300-350 parts of quartz sand, 400-500 parts of river sand, 400-500 parts of ceramic particles and 120-150 parts of deionized water. The silicate cement is fast-hardening sulphoaluminate cement.
3. A UHPC thin-walled pole and a method for preparing the same according to claim 1, characterized in that: The glass fiber has a length of 10-15 mm, and the surface is specially treated to enhance the bonding force with concrete. The special treatment of the glass fiber surface is divided into three main items: chemical treatment, physical treatment and composite treatment. The special surface treatment can increase the friction and chemical bonding between the glass fiber and concrete, and improve the bonding strength between the two. The chemical treatment includes coupling agent treatment and surface coating treatment. During the coupling agent treatment, a silane coupling agent is used to treat the surface of the glass fiber. One end of the coupling agent molecule reacts chemically with the silanol group on the surface of the glass fiber to form a chemical bond, and the other end is combined with the cement hydration product in the concrete. The coupling agent selects γ-aminopropyltriethoxysilane coupling agent, which can form an organic silicon layer on the surface of the glass fiber, enhance the bonding force with the inorganic components in the concrete, and improve the bonding strength. The coupling agent treatment can increase the chemical bonding between the glass fiber and the concrete, improve the compatibility between the two, and improve the bonding force. During the surface coating treatment, a special polymer coating is coated on the surface of the glass fiber. The polymer coating can select epoxy resin and polyester, which is easy to combine with cement slurry during concrete mixing to form a strong bond.
4. A UHPC thin-walled pole and a method for preparing the same according to claim 3, characterized in that: The physical treatment method includes plasma treatment and surface etching. During the plasma treatment, the surface of the glass fiber is modified by plasma. The high-energy particles in the plasma cause physical and chemical changes on the surface of the glass fiber to increase the surface activity. Polar groups are introduced on the surface of the glass fiber through plasma treatment to improve the interaction with water molecules and cement particles in concrete and enhance the bonding force. During the surface etching, chemical and mechanical methods are used to etch the surface of the glass fiber to increase its surface roughness. The chemical method uses acid and alkali solutions to corrode the surface of the glass fiber to form a microscopic concave-convex structure. Mechanical etching is achieved by sandblasting and grinding. The composite treatment step is composite treatment with nano materials, nano materials are loaded on the surface of the glass fiber, and nano silicon dioxide and carbon nanotubes are selected as the nano materials. Nano silicon dioxide particles are loaded on the surface of the glass fiber by chemical adsorption and physical deposition to form a nano composite structure. The ceramic particles are high-strength wear-resistant ceramics with a particle size of 2-5 mm.
5. A UHPC thin-walled pole and a method for preparing the same according to claim 1, characterized in that: The method comprises the following steps: Sp1. Pole reinforcement: The pole reinforcement skeleton is made of carbon fiber reinforced composite materials. The carbon fiber reinforced composite materials are selected from high-quality carbon fiber prepregs. When preparing the carbon fiber reinforced composite materials, the carbon fiber prepregs are laid on the mold according to the designed laying sequence and fiber direction. Manual laying and automated laying equipment can be used to ensure the uniformity and accuracy of the laying. During the laying process, pay attention to avoid wrinkles, bubbles and gap defects, and use rollers and vacuum bags for compaction and air removal; Sp2, placing the steel bar skeleton of the thin-walled pole (1) into the pole mold, the mold adopts a detachable design to facilitate demoulding and assembly, and the pole mold adopts a Fuda fully automatic pressure-adjustable mold; Sp3, adding the proportion of silicate cement, fly ash microbeads, slag micropowder, high-efficiency water reducing agent, quartz sand, river sand and ceramic particles into a powerful mixer and stirring evenly, then adding deionized water and continuing stirring, the glass fiber is evenly dispersed into the concrete by air jetting, the powerful mixer can make the raw materials fully mixed, improve the uniformity and quality of the concrete, the glass fiber is evenly dispersed into the concrete by air jetting, avoid fiber agglomeration, and improve the performance stability of the thin-walled pole (1), during the stirring process, strictly control the stirring time and speed; Sp4. Place the pole mold on the intelligent centrifuge for centrifugal molding. The intelligent centrifuge automatically adjusts the centrifugal parameters according to the characteristics of the concrete and the specifications of the pole. The intelligent centrifuge automatically adjusts the centrifugal speed, time and acceleration parameters according to the characteristics of the concrete and the specifications of the pole to ensure that the pole achieves the best density and strength during the centrifugal molding process; Sp5. Perform microwave curing on the centrifugally formed pole mold and thin-walled pole (1). During the curing process, a temperature sensor and a humidity sensor are used for real-time monitoring to ensure the curing effect. The temperature and humidity during the curing process are precisely controlled by the temperature sensor and the humidity sensor for real-time monitoring; Sp6. After the microwave curing, the mold is removed, and the thin-walled pole (1) is subjected to surface treatment after demoulding to improve the appearance quality of the thin-walled pole (1). The thin-walled pole (1) is subjected to surface treatment after demoulding. The surface treatment steps are divided into three types: grinding, polishing and spraying. The appearance quality of the pole is improved after the surface treatment.
6. A UHPC thin-walled pole and a method for preparing the same according to claim 5, characterized in that: The powerful mixer is provided with mixing blades and scrapers inside, and the raw materials are quickly and fully mixed by using the powerful mixer with high speed and large torque to improve the uniformity and quality of concrete.
7. A UHPC thin-walled pole and a method for preparing the same according to claim 5, characterized in that: The airflow injection device includes a compressed air source, a nozzle and a control system to accurately control the injection amount and direction of the glass fiber. The compressed air source provides a strong airflow power to inject the glass fiber into the concrete. The nozzle is used to accurately control the injection amount and direction of the glass fiber to ensure that the fiber is evenly distributed in the concrete. The control system can automatically adjust the injection parameters according to the characteristics of the concrete and the specifications of the pole, thereby improving the degree of automation and quality stability of production.
8. A UHPC thin-walled pole and a method for preparing the same according to claim 5, characterized in that: The working mode of the intelligent centrifuge is: slow stage, rotation speed 80r / min, time 3min, rotation speed 160r / min, time 2min; medium speed stage, rotation speed 220r / min, time 1min, rotation speed 260r / min, time 1min; high speed stage, rotation speed 390r / min, time 8min. The three-stage working mode of the intelligent centrifuge gradually increases the centrifugal speed according to the characteristics of concrete and the specifications of the thin-walled pole (1), ensuring that the pole achieves the best density and strength during the centrifugal forming process. The slow stage can make the concrete evenly distributed in the mold to avoid segregation. The medium speed stage can further discharge bubbles and excess water in the concrete to improve the quality of the thin-walled pole (1). The high speed stage can make the pole achieve higher strength in a shorter time, thereby improving production efficiency.
9. A UHPC thin-walled pole and a method for preparing the same according to claim 5, characterized in that: The microwave curing method comprises: using continuous wave microwave with a power of 5-10 kW, a curing time of 2-4 hours and a curing temperature of 60-80°C.
10. A UHPC thin-walled pole and a method for preparing the same according to claim 1, characterized in that: The surface of the thin-walled pole (1) is coated with a waterproof, anti-corrosion and anti-ultraviolet multifunctional coating, the coating being composited from nanomaterials and high molecular polymers, the multifunctional coating protecting the surface of the thin-walled pole (1) from erosion by moisture, corrosive media and ultraviolet rays.
Citation Information
Patent Citations
UHPC thin-wall electric pole and preparation method thereof
CN113149545A
Cited By
Composite material electric pole split type sleeve and connecting method
CN121429231A